Developments in Contact Lens Imaging: New Applications of Optical Coherence Tomography - Joanna Stachura; Małgorzata Seredyka-Burduk; Ilona Piotrowiak-Słupska; Magdalena Kaszuba-Modrzejewska; Jagoda Rzeszewska-Zamiara; Bartłomiej J. Kałużny (Applied Sciences, 2019)
Optical coherence tomography (OCT) is a high-speed and non-contact optical imaging technology widely used for noninvasive cross-sectional imaging of biological objects. Two main OCT technologies have been developed: time domain and Fourier domain technologies. The latter can be further divided into spectral domain OCT, which uses a broadband light source and a spectrometer as a detector, and swept source OCT, which employs a quickly-rotating laser source. Advances in OCT technology have made it one of the most helpful devices in ophthalmic practice. Fourier OCT has revolutionized imaging of the posterior segment of the eye, as well as of anterior structures and has enhanced the ability to diagnose and manage patients. It provides high-resolution information about the tear film, contact lens (CL), a qualitative and quantitative assessment of the anterior eye that is important in CL fitting, and allows possible eye surface changes while wearing CLs to be monitored. Potential swept source OCT technology applications include industrial processes of lens design and quality control. In this paper, we describe clinical applications ant outline a variety of multifunctional uses of OCT in the field of refractive error correction with CLs.